Knowledge of early stunting detection among posyandu cadres and mothers of under-five children: A cross-sectional study in Jambi city - Anindya Gizca Pramesti; Irawati Sukandar; Budi Justitia; Yulinda Fetritura; Denok Tri Hardiningsih (International Journal on Health and Medical Sciences, 2026)
Stunting remained a persistent public health problem in Jambi City, and Tanjung Sari Village recorded the highest number of stunted toddlers within its community health center working area. Since Posyandu cadres and mothers of toddlers served as the two key actors responsible for early stunting detection, this study analyzed the knowledge levels of both groups regarding early detection of stunting in that village. A quantitative descriptive design with a cross sectional approach was applied. Total sampling was used to enroll thirty five active Posyandu cadres, while seventy five mothers of toddlers were selected through simple random sampling. Data were collected using structured questionnaires that had been tested for validity and reliability, and were analyzed univariately. The results showed that most cadres, sixty eight point six percent, and most mothers, fifty eight point seven percent, had a high level of knowledge. However, both groups demonstrated weaker understanding in specific technical areas, cadres in interpreting child growth curves and mothers in recognizing physical signs of stunting and determining the appropriate timing for complementary feeding. These complementary gaps suggested that generally adequate knowledge alone had not been sufficient to lower the stunting burden in the study area. The findings indicated a need for targeted, technically focused, and jointly delivered training for cadres and mothers to strengthen community based early stunting detection efforts in Jambi City.